Proinflammatory Responses of 1-Nitropyrene against RAW264.7 Macrophages through Akt Phosphorylation and NF-κB Pathways - Ping-Kun Tsai (MDPI AG, 2021)
Air pollution is a major environmental and public health problem worldwide. A nitro-polycyclic aromatic hydrocarbon and the most abundant air pollutant in diesel engine exhaust, 1-nitropyrene (1-NP), is caused by the incomplete combustion of carbonaceous organic substances. Macrophages are effector cells of the innate immune cells that provide resistance in the peripheral tissue. The overactivation of macrophages results in inflammation. The generation of proinflammatory cytokines, such as interleukin (IL)-1β, IL-6, and tumour necrosis factor alpha, is induced by 1-NP in a concentration-dependent manner in macrophages. In this study, the production of proinflammatory mediators, such as nitrogen oxide and prostaglandin E2, was induced by 1-NP in a concentration-dependent manner through the expression of iNOS and COX2. The generation of proinflammatory cytokines, iNOS, and COX2 was induced by 1-NP through nuclear factor (NF)-κB p65 phosphorylation and the degradation of its upstream factor, IκB. Finally, Akt phosphorylation was induced by 1-NP in a concentration-dependent manner. These findings suggest that 1-NP exhibits a proinflammatory response through the NF-κB pathway activation due to Akt phosphorylation.